Proficiency of Extracellular Vesicles From hiPSC-Derived Neural Stem Cells in Modulating Proinflammatory Human Microglia: Role of Pentraxin-3 and miRNA-21-5p - Upadhya, Raghavendra; Madhu, Leelavathi N.; Rao, Shama; Shetty, Ashok K. (Frontiers in Molecular Neuroscience, 2022)
Extracellular vesicles (EVs) shed by human-induced pluripotent stem cell (hiPSC)-derived neural stem cells (hNSC-EVs) have shown potent antiinflammatory properties in a mouse macrophage assay and a mouse model of acute neuroinflammation. They can also quickly permeate the entire brain after intranasal administration, making them attractive as an autologous or allogeneic off-the-shelf product for treating neurodegenerative diseases. However, their ability to modulate activated human microglia and specific proteins and miRNAs mediating antiinflammatory effects of hNSC-EVs are unknown. We investigated the proficiency of hNSC-EVs to modulate activated human microglia and probed the role of the protein pentraxin 3 (PTX3) and the miRNA miR-21-5p within hNSC-EVs in mediating the antiinflammatory effects. Mature microglia generated from hiPSCs (iMicroglia) expressed multiple microglia-specific markers. They responded to lipopolysaccharide (LPS) or interferon-gamma challenge by upregulating tumor necrosis factor-alpha (TNF-α) and interleukin-1 beta (IL-1β) mRNA expression and protein release. iMicroglia also exhibited proficiency to phagocytose amyloid-beta (Aβ). The addition of hNSC-EVs decreased TNF-α and IL-1β mRNA expression and the release of TNF-α and IL-1β by LPS-stimulated iMicroglia (proinflammatory human Microglia). However, the antiinflammatory activity of hNSC-EVs on LPS-stimulated microglia was considerably diminished when the PTX3 or miR-21-5p concentration was reduced in EVs. The results demonstrate that hNSC-EVs are proficient for modulating the proinflammatory human microglia into noninflammatory phenotypes, implying their utility to treat neuroinflammation in neurodegenerative diseases. Furthermore, the role of PTX3 and miR-21-5p in the antiinflammatory activity of hNSC-EVs provides a new avenue for improving the antiinflammatory effects of hNSC-EVs through PTX3 and/or miR-21-5p overexpression.